2010
DOI: 10.1261/rna.2036210
|View full text |Cite
|
Sign up to set email alerts
|

Binding and release of the 6S transcriptional control RNA

Abstract: ABSTRACT6S RNA is an important noncoding RNA that regulates eubacterial transcription. In Escherichia coli this RNA binds to the s 70 RNA polymerase holoenzyme and is released by the synthesis of a short product RNA. In order to determine how binding and release are controlled by the 6S RNA sequence, we used in vitro selection to screen a high diversity library containing ;4 3 10 12 sequences for functional 6S RNA variants. Residues critical for binding were found to be located in a ''-35'' region upstream of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
46
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 14 publications
(26 reference statements)
9
46
0
Order By: Relevance
“…Indeed, T1 RNase digestion of the free 6S RNA (S1) under native conditions revealed G136 to be sensitive to T1 RNase (Fig. 1B), consistent with previous secondary-structure models of the 6S RNA (Barrick et al 2005;Shephard et al 2010). After binding and then releasing the 6S RNA from the holoenzyme via pRNA synthesis so as to form the S4 state, G136 became significantly resistant to T1 RNase while the cleavage pattern of G97, G88, G82, G80, and G79, which were not expected to undergo any secondarystructure rearrangement, remained unaffected.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Indeed, T1 RNase digestion of the free 6S RNA (S1) under native conditions revealed G136 to be sensitive to T1 RNase (Fig. 1B), consistent with previous secondary-structure models of the 6S RNA (Barrick et al 2005;Shephard et al 2010). After binding and then releasing the 6S RNA from the holoenzyme via pRNA synthesis so as to form the S4 state, G136 became significantly resistant to T1 RNase while the cleavage pattern of G97, G88, G82, G80, and G79, which were not expected to undergo any secondarystructure rearrangement, remained unaffected.…”
Section: Resultssupporting
confidence: 90%
“…The unbound 6S RNA (S1 state) and the final released 6S:pRNA complex (the S4 state) are devoid of protein and provide simple evidence that a structural rearrangement occurs during the process of 6S RNA release from E. coli RNA polymerase. Having shown that the À10 region can alter both binding and release rate (Shephard et al 2010), we noticed together with others (Wurm et al 2010;Beckmann et al 2012), that the top strand of the conserved downstream helix is complementary to the conserved À10 region (Fig. 1A).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations